The LADP revisited - a multiple regression approach to evaluation - Williams, Arthur R. (Philippine Journal of Public Administration, 1979)
An evaluation of the University of the Philippines-Local Government Center Local Administration and Development Program study reveals its narrative-descriptive nature and lack of empirical-comparative attributes as a research project. In order to redress the deficiencies of the prior investigation, the utilization of a multiple regression approach which permits the study of the relationship of a large number of independent variables on a single dependent variable is suggested. Dealing with both conceptual and measurement problems relating to program evaluation, two conceptual caveats are suggested in designing evaluative researches: (1) a standard of comparison should be made explicit throughout the design and write-up and (2) in any evaluation which involves subjective appraisals of what is being evaluated, the potential "reactive" nature of the subjects must be considered.